Respon Masyarakat Terhadap Kualitas Pelayanan Publik - Frederikus Antonius Mana; anis munfarikhatin (SOCIETAS, 2024)
Public services are closely related to community welfare and public trust in the government. This phenomenon shows that the quality of public services in Merauke Regency is still unequal, especially in terms of service distribution. Real interaction between the community and public servants can be seen in sub-district offices spread across each district in Merauke Regency. This research aims to analyze the public's response to the quality of public services at sub-district offices by involving five sub-variables, namely tangibles, reliability, responsiveness, assurance and empathy. The data collection method uses a questionnaire which was developed based on sub-variables into 32 questionnaire items whose validity was tested. The validation process is carried out to test the validity of the instrument to be used through face validation involving experts. The respondents involved as research samples were sixty people taken randomly from each district. The results of filling out the questionnaire showed that the sub-variables were 25% reliability, 16% responsiveness, 18% assurance, 13% empathy and 28% tangibles. Data is presented through descriptive statistics via tables, recapitulation of scoring results and bar charts. The results of the analysis provide the following facts that the tangibles sub-variable obtained the largest percentage which shows that the physical appearance of facilities, equipment and personnel appearance influences community satisfaction. Therefore, as public servants, employees need to pay attention to service quality which includes four main aspects.